THE INFLUENCE OF LANGUAGE USE AND LANGUAGE ATTITUDE ON THE MAINTENANCE OF COMMUNITY LANGUAGES SPOKEN BY MIGRANT STUDENTS - Leni Amalia Suek (Universitas Islam Negeri Banda Aceh, 2014)
The maintenance of community languages of migrant students is heavily determined by language use and language attitudes. The superiority of a dominant language over a community language contributes to attitudes of migrant students toward their native languages. When they perceive their native languages as unimportant language, they will reduce the frequency of using that language even though at home domain. Solutions provided for a problem of maintaining community languages should be related to language use and attitudes of community languages, which are developed mostly in two important domains, school and family. Hence, the valorization of community language should be promoted not only in family but also school domains. Several programs such as community language school and community language program can be used for migrant students to practice and use their native languages. Since educational resources such as class session, teachers and government support are limited; family plays significant roles to stimulate positive attitudes toward community language and also to develop the use of native languages.